Dynamics and Applications of Photon-Nanostructured Systems - Sarantopoulou, Evangelia (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Nanotechnologies leverage different hierarchical levels of novel technological applications by introducing molecular functionalities into the macroworld. A novel set of applications emerges by integrating photons and quantum information with the nanoworld. The current Special Issue "Dynamics and Applications of Photon Nanostructured Systems" is shaped by innovative ideas with strong, interdisciplinary, fundamental, theoretical, and applied characteristics, and the content covers a wide range of thematic areas in physics, chemistry and engineering. The book comprises twelve original studies and three review articles addressing novel nanodevices, functionalities, nanothermodynamics, chaos, non-linear dynamics, nanoresonators and applications based on photonic nanostructured devices and photon-nanomaterial interactions.